Waste Identification and Improvement in Raw Material Procurement Processes: Identifikasi dan Perbaikan Pemborosan dalam Proses Pengadaan Bahan Baku - Ari Vera Hardiyanti; Dira Ernawati; Nur Rahmawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Efficient raw material procurement is essential for maintaining manufacturing flow, operational stability, and supply chain performance. Specific Background: PT XYZ, a steel plate and pipe fabrication company, faced procurement inefficiencies caused by non-value-added activities, delayed supplier delivery, limited storage capacity, repeated inspection, material returns, and suboptimal warehouse arrangement. Knowledge Gap: Previous studies have widely applied Value Stream Mapping to production processes, yet limited attention has been given to raw material procurement in steel fabrication, particularly through integrated waste mapping and risk prioritization. Aims: This study aimed to identify procurement waste and formulate targeted process recommendations using Value Stream Mapping, Failure Mode and Effect Analysis, and the 5W+1H framework. Results: The current condition showed a total lead time of 482 minutes, dominated by non-value-added activities. Waiting, defect, and overprocessing were the most critical waste categories, with Risk Priority Number values of 336, 315, and 252, respectively. Future Value Stream Mapping reduced total lead time to 318 minutes, yielding a 164-minute reduction. Novelty: The study integrates VSM and FMEA to connect process visualization with risk-based priority setting in raw material procurement. Implications: The findings provide a structured basis for supplier coordination, material quality standardization, inspection simplification, administrative streamlining, and procurement efficiency in steel fabrication operations. Highlights: Initial duration decreased from 482 to 318 after redesign. Waiting, defects, and overprocessing carried the highest risk priorities. The 5W+1H framework directed supplier, quality, inspection, and administration actions. Keywords: Failure Mode and Effect Analysis (FMEA), Raw Material Procurement, Value Stream Mapping (VSM)